Musikalische Neujahrsgedichte 1772-74; 1776 (Zürich Musiksaal, 1772)
In the 17th century music in Zürich was dominated by three collegia musica: the first was ‘zum Chorherrensaal’, followed by the ‘ab dem Musiksaal’ (from 1613) and ‘zur deutschen Schule’ (from 1679). Initially they were concerned only with sacred music, but later also performed contemporary German and Italian secular music. The three societies merged in 1812 to form the Allgemeine Musikgesellschaft Zürich (AMGZ), which since 1813 has produced books on musical subjects in a series of ‘Neujahrsblättern’, the successors to a series of New Year collections of polyphonic pieces published by two of the collegia musica from 1685 and 1713 respectively.
see 04J20, 10B20, 11H13, 26D03, G1-027 and G1-028 for similar collections
The Musikgesellschaft ‘ab dem Musiksaal’ began to publish New Year's pieces in 1685
Collection of fragments of a larger unknown publication (paginated 303-310 with plates nr LXXXVIII and LXXXIX) and other sections in different page dimensions
contains 2 beautiful engravings by Johann Rudolf Holzhalb (1723-1806) after Johann Rudolph Schellenberg (1740-1806)
Keywords: Allgemeine Musikgesellschaft Zürich (Switzerland); 18th Century (1701-1800); Poetry; Education; Vocal music; Religion; Emblem; Moral education; Song; Zürich (Switzerland)